Bioinspired One Cell Culture Isolates Highly Tumorigenic and Metastatic Cancer Stem Cells Capable of Multilineage Differentiation. Issue 11 (28th April 2020) - Wang, Hai; Agarwal, Pranay; Jiang, Bin; Stewart, Samantha; Liu, Xuanyou; Liang, Yutong; Hancioglu, Baris; Webb, Amy; Fisher, John P.; Liu, Zhenguo; Lu, Xiongbin; Tkaczuk, Katherine H. R.; et al.
Abstract: Cancer stem cells (CSCs) are rare cancer cells that are postulated to be responsible for cancer relapse and metastasis. However, CSCs are difficult to isolate and poorly understood. Here, a bioinspired approach for label‐free isolation and culture of CSCs, by microencapsulating one cancer cell in the nanoliter‐scale hydrogel core of each prehatching embryo‐like core–shell microcapsule, is reported. Only a small percentage of the individually microencapsulated cancer cells can proliferate into a cell colony. Gene and protein expression analyses indicate high stemness of the cells in the colonies. Importantly, the colony cells are capable of cross‐tissue multilineage (e.g., endothelial, cardiac, neural, and osteogenic) differentiation, which is not observed for "CSCs" isolated using other contemporary approaches. Further studies demonstrate the colony cells are highly tumorigenic, metastatic, and drug resistant. These data show the colony cells obtained with the bioinspired one‐cell‐culture approach are truly CSCs. Significantly, multiple pathways are identified to upregulate in the CSCs and enrichment of genes related to the pathways is correlated with significantly decreased survival of breast cancer patients. Collectively, this study may provide a valuable method for isolating and culturing CSCs, to facilitate the understanding of cancer biology and etiology and the development of effective CSC‐targeted cancer therapies. Abstract : A bioinspired technology is developed to isolate cancer stem cells (CSCs) by culturing one cell in the nanoliter‐scale hydrogel core of the prehatching embryo‐like core–shell microcapsules. The CSCs are capable of cardiac, neural, osteogenic, and endothelial differentiation, and are highly tumorigenic, metastatic, and drug resistant. The technology may be valuable for understanding cancer biology/etiology and developing CSC‐targeted effective cancer therapies.